DNA metabarcoding reveal hidden diversity of periphytic eukaryotes on marine Antarctic macroalgae - PAULO EDUARDO A.S. CÂMARA; FRANCIANE MARIA PELLIZZARI; FABYANO A.C. LOPES; EDUARDO T. AMORIM; FÁBIO L.V. BONES; DAFNE A. ANJOS; MICHELINE CARVALHO-SILVA; PETER CONVEY; LUIZ HENRIQUE ROSA (Anais da Academia Brasileira de Ciências)
Abstract Polar marine macroalgae thrive in extreme conditions, often displaying geographic isolation and high degree of endemism. The “phycosphere” refers to the zone around the algae inhabited by microrganisms. Our study used DNA metabarcoding to survey the eukaryotic communities associated with seven seaweed species obtained at King George Island (South Shetland Islands, maritime Antarctic), including two Rhodophyta, two Chlorophyta and three Phaeophyceae. The ITS2 region was used as a barcode and our analysis yielded 77 eukaryotic ASVs spanning five Kingdoms (Fungi, Metazoa, Chromista, Protozoa, and Viridiplantae) and ten phyla (Ascomycota, Basidiomycota, Cercozoa, Ciliophora, Ochrophyta, Amebozoa, Chlorophyta, Rhodophyta, Bryophyta and Cnidaria). Additionally, we identified 14 potential new occurrence records for Antarctica. Ciliates and green algae were the most species-rich groups. The most abundant assigned associated species was Monostroma angicava (Chrorophyta). Within the macroalgal, the Chlorophyceans Ulothrix sp. hosted the greatest number of taxa, followed by Monostroma hariotii. Our data suggested that Antarctic macroalgae host a rich diversity of associated organisms and the biodiversity associated with the phycosphere remains underestimated.